Caddie Woodlawn - Brink, Carol Ryrie; Hyman, Trina Schart (New York Aladdin Paperbacks, 1962)
Caddie is brave, and her story is special - because it's true, based on the life and memories of carol ryrie brink's grandmother, the real caddie woodlawn
American Corner
Winner Of The Newbery Medal
11
Keywords: English Fiction; English Stories